Semito-Hamitic or Afro-Asiatic consonantism and lexicon: Episodes of a comparative research II: The “old school” of Egypto-Semitic (Part 2: Post-war phase) - Takács, Gábor (Lingua Posnaniensis, 2023)
My retrospective survey on the past and present trends in the comparative research of Semito-Hamitic / Hamito-Semitic (SH / HS, resp.) or Afro-Asiatic (AA) phonology (first of all consonantism), root structure and lexicon has been segmented into eleven episodes according to diverse (often overlapping in time) trends. This series of studies is now under way and will be presented part by part in a series of papers. The present paper surveys the post-war history (second half of the 20th century) of a rather introverted and fossilized special branch of comparative studies that has been arbitrarily focusing on a forced comparison of just Semitic and Egyptian, which was split off for more than a whole century by now from mainstream Semito-Hamitic studies at the end of the 19th century.